Hydrogen Storage in Offshore Salt Caverns for Reducing Ships Carbon Dioxide Footprint - Vlăducă, Iulian; Nechifor, Cristian Valentin; Vasile, Mirela-Letiţia; Suciu, Cosmin Petru; Badea, Petre Gabriel; Stănescu, Teodor; Nicoară, Răzvan-Edmond; Prisăcariu, Emilia Georgiana; Stanciuc, Ramona-Manuela; Popescu, Sorin; et al. (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Global shipping activity emits significant amounts of GHG (Greenhouse Gas) emissions, estimated to be around 2-3% of total global GHG emissions. Studies have been made for hydrogen refuelling hubs in the Pacific area, for container ships, that are the worst polluting sources in the oceans. The present paper will show an idea for creating such refuelling hubs using salt cavern for hydrogen storage in Black Sea, and also in other offshore places where the geological formations allow it. The study will allow also the using of hydrogen in military purposes for refuelling the coastal patrol ships or tactical warships like Romanian frigates.